New museum theory and practice an introduction - Marstine, Janet (Malden, Massachusetts Blackwell, 2008)
New Museum Theory and Practice is an original collection of essays with a unique focus: the contested politics and ideologies of museum practice. This lively introduction, comprised of essays authored by curators, archivists, scholars, teachers, and conservators from around the world including the Tate, the Smithsonian, and the Experience Music Project and from all levels of museum studies, examines the incendiary issues currently raging in the field. Complete with editorial introductions, questions for students, and a comprehensive bibliography, the volume surveys the concerns of the museum in language accessible to undergraduate and graduate students of art history, studio art, and museum studies
Electronic reproduction.
Keywords: Museum exhibits; Museum exhibits -- Political aspects; Museum techniques; Museums -- Philosophy